Ovulation time in suckled beef cows is anticipated by use of low doses of progesterone and temporary calf removal on fixed timed AI protocol - Carvalho, E. R. [UNESP]; Martins, T. [UNESP]; Lamb, G. C.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2016)
This study was designed to evaluate the effect of concentrations of P4 during a fixed-time artificial insemination (TAI) protocol and 48 hours temporary calf removal (CR; i.e., calves were temporally weaned for 48 hours) or treatment with 300 IU of eCG on ovulation time in suckled beef cows. One hundred and fourteen Nellore cows were estrous synchronized by receiving an intravaginal P4 releasing device containing 1.9 g of P4 (CIDR) plus 2.0-mg estradiol benzoate on Day 0, 12.5-mg dinoprost tromethamine on Day 7, and CIDR removal plus 0.5-mg estradiol cypionate on Day 9. Concentrations of P4 (P4 conc.) were manipulated by insertion of a new CIDR containing 1.9 g of P4 (CIDR1) or a CIDR previously used for 9 days (CIDR2), 18 days (CIDR3), or 27 days (CIDR4). On Day 9, within CIDR uses, cows received either CR or eCG. On Day 11 (48 hours after CIDR removal), all cows received a single TAI. Estrus was observed twice, a day between Day 9 and TAI. Ovulation by 60 hours or 72 hours after CIDR removal was defined as the disappearance of the largest follicle (LF) detected on Day 11 and presence of CL on Day 18, determined by transrectal ultrasonography. Cows ovulating after 72 hours were deemed to have a dominant follicle at 60 hours and 72 hours but also had a CL on Day 18. Serum P4 conc. were evaluated on Days 9, 11, and 18. Cows from CIDR4 + CR treatment ovulated at 60 hours (53.3%) tended to be greater (P = 0.07) than CIDR4 + eCG (21.4%). For the remaining treatments, this effect was not detected (CIDR1 + eCG: 6.3% vs. CIDR1 + CR: 0.0%; CIDR2 + eCG: 6.7% vs. CIDR2 + CR: 12.5%; CIDR3 + eCG: 0.0% vs. CIDR3 + CR: 25%). As a consequence, the percentage of cows from CIDR4 + CR treatment ovulating by 72 hours (26.7%) was lesser (P < 0.05) than that of cows in the CIDR4 + eCG treatment (78.6%), but for the remaining CIDR uses ovulation was not affected. The analysis of ovulating time revealed that earlier ovulation was associated (P < 0.01) to: (a) lesser P4 conc. on Day 9 (2.69b, 3.36a, and 3.82a ng/mL, standard error of the mean [SEM]: 0.12); (b) greater LF on Day 11 (12.46a, 12.09a, and 11.06b mm, SEM: 0.34); (c) greater estrus rate (94.1%a, 80.0%a, and 28.6%b), for ovulation at 60 hours, 72 hours, or >72 hours, respectively. Thereafter, previously used CIDR resulted (P < 0.01) in lesser P4 conc. on Day 9 (4.84a, 3.24b, 3.00b, and 2.50c ng/mL, SEM: 0.12), greater LF (10.50b, 12.07a, 11.98a, and 12.33a mm, SEM: 0.18) but only CIDR4 increased (P < 0.05) estrus rate (53.1%b, 65.6%b, 57.9%b, and 90.3%a), for CIDR1, CIDR2, CIDR3, and CIDR4, respectively. In conclusion, cows with low concentrations of P4 during a TAI protocol exhibited increased follicle diameter and an increased rate of estrus. This resulted in a greater percentage of cows ovulating by 60 hours when they had experienced calf removal.
Keywords: Dominant follicle; eCG; Estrus behavior; Nellore cows